Kinetic analysis of the wrist and fingers during fastball and curveball pitches - Shibata, S.; Kageyama, M.; Inaba, Y.; Yoshioka, S.; Fukashiro, S. (European Journal of Sport Science, 2022)
This study had two objectives: (a) revealing kinetic parameter differences at the fingers during a fastball and curveball, and (b) examining timing control between the wrist and finger torques. The participants were eight baseball pitchers. The kinetics of the wrist and fingers were calculated using an inverse dynamics method. The peak torque and work of finger adduction during the curveball was significantly larger than that during the fastball. During the fastball pitch, the maximal correlation coefficient between the wrist flexion torque and finger flexion torque was very high (r = 0.94 ± 0.05). The reasons for this result are twofold: (a) the extrinsic finger muscles cross the wrist (biarticular muscle) and (b) the wrist flexion torque during the fastball pitch acts in the direction of acceleration of the ball. During the curveball pitch, we found two typical types of wrist and finger torque control. Furthermore, the two pitchers exerted large wrist extension and radial torque, and finger adduction torque. Although the other six pitchers hardly exerted these torques, they exerted wrist flexion torque predominantly. It was considered that the six pitchers selected wrist flexion torque as the control for the fastball and curveball pitch to confuse the batter.